Citologia para estudantes surdos: uma unidade de ensino potencialmente significativa - Tavares, Eliane Barth (2018)
Taking into account that deaf students’ learning depends on another language which is not Portuguese, we consider it important to use Brazilian Sign Language as a language of instruction for teaching and learning curriculum disciplines in a meaningful way, including Biology Teaching, mainly abstract and complex contents regarding Cytology. For this reason we have elaborated an investigative path in order to build a Potentially Meaningful Teaching Unit (PMTU) to teach Cytology using Brazilian Sign Language, based on visual pedagogy, to first-year deaf students of inclusive high schools in Rio Branco, Acre State. In this perspective, we chose Ausubel’s Meaningful Learning Theory (AUSUBEL; NOVAK; HANESIAN, 1980) as theoretical framework and the action research methodology to promote the active participation of individuals and drawing up a Didactic Guide to teach Biology for deaf students. This research was conducted in two phases, having the first one involved the description of individuals’socio-educational profiles through survey forms or interviews. The second phase encompassed the development of a PMTU which was initially carried out with the identification of previous knowledge concerning to Cytology followed by a carefully conducted planning to enable a richer educational environment with presentation of diverse resources (such as animations, learning objects, images, videos, microscopy experiments and instructional Concept Maps) explained in Brazilian Sign Language so that the relations between previous and new knowledge were explicitly presented. During the elaboration of this study, evidences of students learning were assessed via Concept Maps (NOVAK; GOWIN, 1999). Concept Maps analyses were carried out via Topological Taxonomy (CAÑAS et al., 2006) and Semantic Taxonomy (MILLER; CAÑAS, 2008). Results of socio-educational diagnosis detected 18 deaf students as investigation subjects whose ages range between 14 and 22 years old, being the majority (64%) of them males. Levels of hearing loss varied from moderate to profound, in which the human voice could not be detected, nevertheless four students could not communicate well using Brazilian Sign Language. Low language performance is caused by lack of contact with proficient users in school, since neither classmates, teachers and academic community do not communicate with them using Brazilian Sign Language, except by the Sign Language Interpreter. Not even teachers working in Multifunctional Resource Rooms which were supposed to provide Special Educational Services in Brazilian Sign Language have language proficiency, and that is why deaf students do not attend this school place. Throughout PMTU development the use of visual resources was an important factor to ensure the comprehension of the words without corresponding signs in Brazilian Sign Language. Furthermore the Concept Maps were helpful resources as evidence of learning in Cytology Teaching for deaf students. Ith demonstrate the evolution and major integration between concepts as new knowledge were related to their previous one and they became more skillful with the software.